A longitudinal study on stress sources perceived by Chilean dental students (2018)
Introduction: Establishing the perception of academic stress by university students is highly relevant to obtain valuable feedback on the efficiency and acceptability of educational methods.Objective: To evaluate the differences in stress factors perceived by first-year dental students during the first and second semesters according to gender.Materials and methods: Exploratory, non-experimental, longitudinal descriptive study. The Spanish version of the Dental Environment Stressors (DES) questionnaire was applied, adapted and validated for the dental students of the San Sebastián University (Concepción, Chile) in May and October 2016. The sample consisted of 83 first-year students evaluated. A general comparison of the variables under study (stress and its dimensions) was made for both periods, considering genders and using the Student’s t-test. Fisher’s F test was used after estimating whether or not there was equality of variances between the groups.Results: The second measurement revealed that the “clinical training” dimension in women was the only component that showed significant differences with values above the mean.Conclusion: The perception of stress was estimated for all items of the DES questionnaire, obtaining a higher score in the “clinical training” dimension in women.